Integrating Innovation with Tradition: Drones and Takaful in Mass Disaster Victim Identification - Ahmad Farouk Zulkifli (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
The adoption of drone technology by takaful operators for disaster victim identification represents a promising advancement in disaster management. This qualitative study investigates the perspectives of key stakeholders on integrating drones into takaful practices during mass disasters. Through in-depth interviews with subject matter experts—including accounting professionals, shariah scholars, drone technologists, first responders, actuaries, financial regulators, takaful operators, and loss adjusters—this research explores the multifaceted considerations influencing drone adoption. Thematic analysis of the interview data, conducted using ATLAS.ti, reveals critical insights into technological benefits, operational challenges, regulatory compliance, ethical concerns, and shariah compatibility. Experts highlight the potential of drones to enhance the efficiency and accuracy of victim identification, which aligns with the takaful principle of mutual assistance. However, significant barriers such as regulatory hurdles, data privacy issues, and the need for shariah-compliant frameworks are identified. The study provides a comprehensive understanding of the enablers and obstacles in adopting drone technology from a takaful perspective, offering strategic recommendations to address these challenges. By fostering collaboration among technology developers, regulatory authorities, and takaful operators, this research underscores the importance of an integrated approach to improve disaster response and victim identification processes. The findings contribute to the evolving discourse on the intersection of technology and takaful, paving the way for innovative and ethical disaster management solutions.